Investigating the Mechanism of the Catalytic Intramolecular Aza-Wittig Reaction Involved in the Synthesis of 2-Methylbenzothiazole from the Perspective of Bonding Evolution Theory - Adjieufack, Abel Idrice; Champagne, Benoît; Liégeois, Vincent (Synthesis, 2023)
Bonding evolution theory has been used at the density functional theory level [ωB97X-D exchange-correlation functional, 6-311G(d,p) basis set, and solvent (toluene) effects with polarizable continuum model] to unravel the reaction mechanism of the intramolecular aza-Wittig reaction of 2-(acetylthio)phenyl isocyanate (1) catalyzed by 3-methyl-1-phenyl-2-phospholene 1-oxide (2) to form 2-methylbenzothiazole (3). The reaction involves four steps (transition states) corresponding to (1) the formation of a cycloadduct (O–C then P–N bonds), (2) a decarboxylation leading to the formation of an iminophosphorane, and (3) an intramolecular [2+2] cycloaddition (N–C then P–O bonds) followed by (4) a retro [2+2] cycloaddition (cleavage of the P–N then O–C bonds) to get the product and regenerate the catalyst. Step 1 is the rate-determining step with an activation Gibbs free enthalpy of 21 kcal mol–1 and it is favored with respect to a competitive pathway leading to the formation of another cycloadduct (P–C then O–N bonds). The whole reaction is exergonic with a Gibbs free energy decrease of 31 kcal mol–1, associated with the liberation of a CO2 molecule and the formation of the aromatic benzothiazole. Following the scale of Domingo, the successive steps of the reaction have a polar nature.
Keywords: Wittig reaction; bonding evolution theory; DFT calculations; 2-methylbenzothiazole synthesis; aza-Wittig